TiO2 Nanoparticles in Cancer Therapy as Nanocarriers in Paclitaxel’s Delivery and Nanosensitizers in Phototherapies and/or Sonodynamic Therapy - Tonelli, Fernanda M.P.; Tonelli, Flávia C.P.; Cordeiro, Helon G. (Current Pharmaceutical Biotechnology, 2024)
Nanomaterials have been offering improvements in different areas due to their unique characteristics, but cytotoxicity associated with their use is still a topic that concerns researchers. Causing cell death, at first glance, may seem to be a problem and the studies regarding signaling pathways involved in this toxicity are still in their infancy. However, there are scenarios in which this feature is desirable, such as in cancer treatment. Anti-cancer therapies aim to eliminate the cells of malignant tumors as selectively as possible. From this perspective, titanium dioxide (TiO2) nanoparticles (NPs) deserve to be highlighted as important and efficient tools. Besides being able to induce cell death, these NPs can also be used to deliver anti-cancer therapeutics. These drugs can be obtained from natural sources, such as paclitaxel (an antitumoral molecule derived from a vegetal source). The present review aims to explore the recent knowledge of TiO2 NPs as nanocarriers (promoting the nanodelivery of paclitaxel) and as nanosensitizers to be used in phototherapies and/or sonodynamic therapy aiming to treat cancer. Signaling pathways triggered by this nanomaterial inside cells leading to apoptosis (a desirable fate when targeting tumor cells) and challenges related to the clinical translation of these NPs will also receive attention.
Keywords: paclitaxel nanodelivery